The Effects of High-Intensity Interval Training on Exercise Capacity and Prognosis in Heart Failure and Coronary Artery Disease: A Systematic Review and Meta-Analysis - Cuihua Wang; Jun Xing; Baoli Zhao; Yahui Wang; Lizhuang Zhang; Yebo Wang; Mingqi Zheng; Gang Liu (Hindawi-Wiley, 2022)
Objective. The purpose of this study is to compare the effects of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on exercise capacity and several prognostic markers in patients with coronary artery disease (CAD) and heart failure (HF). Methods. This systematic review is registered on the INPLASY website (number: INPLASY202080112). We conducted a comprehensive search in eight databases of literature before September 13, 2019. Trials comparing HIIT and MICT in participants with CAD or HF aged 52-78 years were included. Exercise capacity (peak oxygen consumption (peak VO2)) and prognostic markers, such as the anaerobic threshold (AT), minute ventilation/carbon dioxide production (VE/VCO2) slope, left ventricular ejection fraction (LVEF), and prognostic value of the predicted VO2 max per cent (the predicted VO2 peak (%)) were examined. Results. A total of 15 studies were included comprising 664 patients, 50% of which were male, with an average age of 60.3±13.2 years. For patients with CAD, HIIT significantly improved peak VO2 values (95% CI 0.7 to 2.11) compared with MICT, but peak VO2 values in patients with HF did not seem to change. For training lasting less than eight weeks, HIIT significantly improved peak VO2 values (95% CI 0.70 to 2.10), while HIIT lasting 12 weeks or longer resulted in a modestly increased peak VO2 value (95% CI 0.31 to 5.31). High-intensity interval training significantly increased the AT when compared with MICT (95% CI 0.50 to 1.48). High-intensity interval training also caused a moderate increase in LVEF (95% CI 0.55 to 5.71) but did not have a significant effect on the VE/VCO2 slope (95% CI −2.32 to 0.98) or the predicted VO2 peak (95% CI −2.54 to 9.59) compared with MICT. Conclusions. High-intensity interval training is an effective therapy for improving peak VO2 values in patients with CAD. High-intensity interval training in the early stage (eight weeks or fewer) is superior to MICT. Finally, HIIT significantly improved prognostic markers, including the AT and LVEF in patients with CAD and HF.